Rethinking forest monitoring for more meaningful global forest landscape change assessments. (1st September 2022) - Estoque, Ronald C.; Johnson, Brian Alan; Dasgupta, Rajarshi; Gao, Yan; Matsuura, Toshiya; Toma, Takeshi; Hirata, Yasumasa; Lasco, Rodel D.
Abstract: Forest ecosystems play an indispensable role in addressing various pressing sustainability and social-ecological challenges such as climate change, biodiversity loss, and ecosystem services deterioration, hence the monitoring of the world's forests is crucial. As part of the global forest assessment workflow, a forest is generally classified and mapped based on land use and/or using a tree canopy cover threshold. In this paper, we examine the limitations of this approach and argue that the use of a land use-based forest definition and tree canopy cover thresholds can overlook forest degradation and enhancement, disguise the actual status of forest landscapes, and misinform management planning. These limitations can delay the development and implementation of forest restoration and conservation measures. To help overcome these issues, we propose some enhancements to the global forest assessment workflow, including the sharing of spatial data and inclusion of tree canopy cover estimates in assessment reports. Such enhancements are needed to achieve more meaningful forest monitoring and reporting in the context of global environmental initiatives, such as those related to climate change mitigation and adaptation, forest restoration, biodiversity conservation, and ecosystem services monitoring. Highlights: We examine the use of land use-based forest concept and tree canopy cover thresholds in forest monitoring. This approach for forest monitoring can overlook forest degradation and enhancement. It can disguise the actual status of forest landscapes and misinform management planning. It can delay the development and implementation of forest restoration and conservation measures. We propose some enhancements to the global forest assessment workflow.